Pendekatan Aktif dan Inovatif dalam Pembelajaran Bahasa Arab untuk Anak - Husein Fadzlullah; Faruq Abdul Mu’id (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
The studThis article discusses methods of learning Arabic for children with an active and innovative approach. Given the importance of teaching Arabic from an early age, this study identifies various creative methods that can improve children's language skills effectively. Through a qualitative and quantitative approach, this article explores various techniques such as educational games, the use of digital media, and art-based activities. Research results show that these methods not only improve children's language skills but also make the learning process more interesting. This article also discusses the challenges encountered in the application of such methods and provides suggestions for addressing them.